Mitigating Safety Risks in Information Systems: A Self-Adaptive Approach - Shuja Mughal; Jens H. Weber; Assad Abbas (IEEE Access)
With various benefits of Information Systems (IS), there are increasing apprehensions regarding their safety implications. Despite researchers’ investigation and publication of the safety advantages of IS, several case studies have revealed distinct, potentially fatal issues and safety risks even with the use of IS. Accidents occur due to differences between the process models (mental models) employed by users and the actual characteristics of the operation. This is particularly true for accidents consisting of interactions between users and safety-critical IS. These users’ process models and Situational Awareness (SA) generate incidents that pose safety hazards to human lives. This ambiguity in the process model and SA may be due to the user’s perspective of what the system does and the actual characteristics of the system. The literature on the user’s process model and SA has been extensively employed in technological systems, but its application to socio-technical systems has been limited. We have identified problems that constitute a potential safety risk with the IS. The issues correspond to the lack of alignment between the process model and situation awareness about the user when interacting with the IS. This lack of alignment and SA can result from various circumstances, including interruptions, multitasking, and cognitive overload. These disruptions make it more challenging to understand the circumstances, which may result in mistakes, inefficiencies, and even safety hazards. Knowing about these interruptions, an information system (IS) could adjust its usage procedure in real time to lessen the disruption’s impact. Such a system could aid in restoring SA by identifying, reacting and adapting to these disturbances. This self-adaptive system (SAS) is used in our study to investigate the impact of an adaptive IS on SA, usability and safety performance outcomes. The findings of this study and the controlled experiment shed light on how system adaptation can mitigate the negative impacts of interruptions, improving safety, effectiveness, efficiency, SA, usability, frustration, and decision-making.